Is sarcopenia a risk factor for anastomotic leak in colorectal cancer surgery? - Chinelli, Javier; Medina, Adrián; Moreira, Emilia; Rodríguez, Gustavo (Revista Argentina de Cirugía, 2026)
Background: Sarcopenia, defined as the loss of muscular mass and strength, is a natural consequence of aging, but it also linked to other conditions, including cancer and has been associated with worse postoperative outcomes. Objective: The aim of this study the associations between psoas muscle area and psoas muscle density and anastomotic leak (AL) in colorectal cancer surgery. Material and methods: Patients undergoing elective curative intent surgery for colorectal cancer with primary anastomosis between January 2018 and June 2024 were included. In all cases, the measurement of psoas muscle area and density was determined on the preoperative computed tomography scan at the level of the first and third lumbar (L3) vertebrae. The relationship between both parameters with AL was determined separately in two groups of patients: those who underwent colon resection and those who underwent rectal resection. Results: A total of 135 patients were analyzed: 88 colectomies (16 cases of AL and 72 controls without AL) and 47 rectal resections (7 with AL and 40 controls without AL). There was no association between qualitative variables and AL. Of the quantitative variables, there was only a non-significant association with blood albumin level in the colectomy group (OR 0.286; IQR 0.112- 0.737). Conclusion: In the present study there was no association between AL and muscle mass as assessed by psoas muscle area and density. Anastomotic leak is a complex and multifactorial phenomenon that requires consideration of other variables